Азербайджан и Турция – торгово-экономические отношения: достижения и перспективы - Абдуллаева, Х. (Культура народов Причерноморья, 2014)
В статье рассматривается экономическое сотрудничество Азербайджана и Турции в
постсоветский период. Подробно анализируется достигнутый уровень двухсторонних экономических
связей между этими странами. Рассматриваются юридическая база двухсторонних отношений и
приоритетные сферы экономического сотрудничества. Исследуются проблемы, связанные с
национальными законодательствами, требованиями таможенных и налоговых структур двух стран.
Предлагаются рекомендации по развитию более широких экономических отношений между двумя
странами. У статті розглядається економічна співпраця Азербайджану і Туреччини в пострадянський
період. Детально аналізується досягнутий рівень двосторонніх економічних зв'язків між цими країнами.
Розглядаються юридична база двосторонніх відносин і пріоритетні сфери економічної співпраці.
Досліджуються проблеми, пов'язані з національними законодавствами, вимогами митних і податкових
структур двох країн. Пропонуються рекомендації з розвитку більш широких економічних відносин між
двома країнами. This article discusses economic cooperation between Azerbaijan and Turkey in the post-Soviet
period. Detailed analysis of the achieved level of bilateral economic relations between the two countries.
Turkey first countries to recognize the state independence of Azerbaijan. November 9, 1991, Turkey recognized
the independence of Azerbaijan, and diplomatic relations were created January 14, 1991 [11]. Bilateral
economic relations between Azerbaijan and Turkey over the last 20 years and have achieved a high quality
speakers, which could be an example and a model for other neighboring countries. In relations between Turkey
and Azerbaijan, as in the first years of independence, in recent years have also been carried out interesting
innovations.
As a result, political rigidity and facilitation of the head of state political and economic ties between Azerbaijan
and Turkey, developing, reached the level of strategic cooperation. Accomplished in life in the field of energy, oil
and gas projects of Baku-Tbilisi - Ceyhan and Baku -Tbilisi - Erzurum gas play an important role not only
energy security for our country, but also for Europe.
Considered the legal basis of bilateral relations and priority areas of economic cooperation. The problems
connected with national legislation, the requirements of customs and tax structures of the two countries.
Provides guidance for the development of the broader economic relations between the two countries.
The relevance of this work is due to the total number of investments made by Turkish firms in the oil and non-oil
sectors and play an indispensable role in the socio-economic development of Azerbaijan exceeded $ 6 billion.